The Role of Laboratory Measurements on D-dimer Level in Patients with COVID-19: A Retrospective Study - Abdulah, Deldar Morad; Ahmed, Ghazwan Fawzi; Ismaeel, Qais Ibraheem (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Inflammation may raise the concentration of D-dimer level in COVID-19 patients. There is no consensus on the role of inflammation on the D-dimer level in the literature. We aimed to examine the role of inflammation in D-dimer level in COVID-19 patients. Methods: The patients who were suspected of COVID-19 disease were referred by one of the medical doctors to a private medical lab between 1 July and 30 November 2020. The patients with COVID-19 infection were diagnosed using a combination of IgG and IgM antibodies. The confirmed laboratory patients were considered cases (n=204) and others as healthy controls (n=440) in this case-control investigation. Results: In this study, the patients were older compared to the healthy controls; 54.5 vs. 51.5 years; P=0.0251. The patients had a significantly higher concentration of D-dimer (483.5 vs. 318 µg/ml; elevated prevalence: 48.53% vs. 22.95%; P<0.001) and significantly higher median CRP concentration compared to the healthy controls (89.0 vs. 36.63 IU/ml (P<0.001), respectively. The patients and controls had a similar median ferritin concentration. The nominal logistic regression model showed that D-dimer (P=0.00274) was the only variant factor between the COVID-19 patients and healthy controls. The CRP concentration was not shown to determine the D-dimer levels in COVID-19 patients (P=0.4713). Conclusions: This study showed that patients with COVID-19 have elevated levels in CRP and D-dimer. The study did not confirm the role of inflammation in elevating D-dimer in COVID-19 patients. The inflammatory and thrombosis markers are required to be measured in COVID-19 patients with different severities at various follow-up periods in a prospective study.